2011
DOI: 10.1115/1.4003653
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pulsed Film Cooling on Leading Edge Film Effectiveness

Abstract: Detailed film effectiveness measurements have been made on a cylindrical leading edge surface for steady and pulsating flows. The film hole is off centered by 21.5 deg from the centerline and angled 20 deg to the surface and 90 deg from the streamwise direction. Two jet-to-cross-flow velocity ratios have been considered: VR=1 and 2, which correspond to blowing ratios of 1 and 2, respectively. The pulsating frequency is 10 Hz and the duty cycle is 50%. Comparisons between film effectiveness with a pulsating fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
1
8
0
1
Order By: Relevance
“…This result is consistent with previous research of El-Gabry and Rivir [9]. While comparing to the steady flow, the sinusoidal wave pulsed flow decreases film cooling effectiveness at BR ¼ 0.5, but increases film cooling effectiveness and improves film coverage effect at BR ¼ 0.75 and BR ¼ 1.0.…”
Section: Effects Of Br On Film Cooling Effectivenesssupporting
confidence: 95%
See 1 more Smart Citation
“…This result is consistent with previous research of El-Gabry and Rivir [9]. While comparing to the steady flow, the sinusoidal wave pulsed flow decreases film cooling effectiveness at BR ¼ 0.5, but increases film cooling effectiveness and improves film coverage effect at BR ¼ 0.75 and BR ¼ 1.0.…”
Section: Effects Of Br On Film Cooling Effectivenesssupporting
confidence: 95%
“…Ekkad et al [8] used a transient infrared technique to investigate the effects of jet pulsation and DC on film cooling effectiveness and heat transfer on a circular LE, their results indicated that reducing the DCs leads to higher film cooling effectiveness and lower heat transfer coefficients, and the influences of jet frequencies (5 Hz, 10 Hz and 20 Hz) on the film cooling effectiveness and heat transfer coefficient are not important. El-Gabry and Rivir [9] experimentally measured the film cooling effectiveness on a cylindrical LE surface, and compared the cooling effect of steady flow with that of pulsating flow. Their comparison showed that at the same BR, the film cooling effectiveness is reduced by a factor of 2 when the flow is pulsed, and therefore they deemed that it is necessary for further investigation to fully understand the pulsating performances, and to confirm when pulsating can enhance film cooling effectiveness.…”
Section: Introductionmentioning
confidence: 98%
“…It is clear from the studies above [10][11][12][13][14] that the reported results are not consistent with both positive and negative effects of coolant pulsations on film cooling. Further, in the experimental studies reported in the literature, there is a significant amount of deviation between the desired instantaneous blowing ratio and the actual delivered pulse form.…”
Section: Introductionmentioning
confidence: 83%
“…They also observed that the pulsed jet outperformed the steady jet with the same time-averaged blowing ratio. El-Gabry and Rivir [12] studied the effect of pulsation on the leading edge film cooling on the same geometry [11], and observed that the film effectiveness of the pulsed cases were lower than that of steady jets with the same time-averaged blowing ratios.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that three parameters related to pulsation (frequency, blowing ratio, and duty cycle) affect the film cooling performance. El-Gabry and Rivir (2012) investigated the effect of coolant jet pulsation on a leading edge surface experimentally and reported that the film cooling effectiveness was decreased by a factor of 2 compared to that at a steady state [25]. The blowing ratios were 1.0 and 2.0, the frequency of the pulsation was 10 Hz and the duty cycle was set as 50%.…”
Section: Introductionmentioning
confidence: 99%